Design and Development of an Instructional Program for Teaching Programming Processes to Gifted Students Using Scratch - Yıldız Durak, Hatice; Güyer, Tolga (IGI Global, 2022)
This chapter examines practical applications of an educational program designed to teach Turkish gifted second, third, and fourth grade students programming using Scratch, an online programming website (https://scratch.mit.edu). This qualitative research study was conducted with gifted identified students in an elementary school in Ankara's Altındağ district. Qualitative data collection methods were used. The study found program strengths included practical orientation, student independence, student free expression, computer literacy, and interdisciplinary connections. Additionally, providing a variety of tools and equipment, using Scratch, having a course web site, and on-line resource sharing were also seen as strengths by the participants. Perceived weaknesses were technical difficulties, the limited number of course hours, some of Scratch's negative features, inadequate help at particular points, and negative situations caused by gender and grade level differences. Results indicate preliminary knowledge of participant computer literacy as important to programming success. © 2022 Elsevier B.V., All rights reserved.
Keywords: [No Keywords]